Surgical thrombectomy after large vessel ischaemic stroke – a case report - Peixoto, João (2023)
BACKGROUND: Endovascular mechanical thrombectomy (MT) changed acute ischaemic stroke management and is considered the standard of care for patients with proximal anterior circulation occlusion. MT improves functional independence, without an increase in mortality. Despite its advantages, up to 20% of patients treated with MT do not have successful recanalization, leading to poor clinical outcome. We present a case of an acute ischaemic stroke of the anterior circulation due to occlusion of the common carotid artery successfully submitted to surgical thrombectomy after failed MT. CASE REPORT: A 43-year-old male, with prior history of diabetes, hypertension, dyslipidaemia and heart failure was admitted at the emergency unit with acute bilateral lower limb ischaemia, due to cardioembolic phenomena. He was submitted to bilateral femoral thrombectomy and started endovenous unfractionated heparin. On the fifth postoperative day he developed sudden depression of cognitive status and left side hemiplegia of brachial predominance. Computed tomography angiography revealed an occlusion of brachiocephalic trunk, right subclavian artery and common carotid artery, preserving its branches. MT, performed by interventional neuroradiology, was unsuccessful (no recanalization or clinical improvement). After multidisciplinary discussion, the patient underwent urgent surgical thrombectomy through carotid and transaxillary approaches. Postoperatively, the patient’s mental status and left sided motor function recovered progressively over time. Three months after, patient maintains anticoagulation with warfarin, without neurological sequalae. CONCLUSION: The low rate of recanalization and poor clinical outcome after MT failure underlines the need for alternative rescue approaches. Surgical thrombectomy could represent a lifeline. More studies are needed to corroborate its efficacy in patients with anterior circulation acute ischaemic stroke.